Penetapan Kadar Kalsium Pada Kacang Hijau (Vigna Radiata L.) Secara Kompleksometri - Refdia Yola; Renatalia Fika (Journal Pharma Saintika, 2021)
Green beans (Vigna radiata L.) contain many nutrients needed by the body, one of which is calcium. In this study, a complexometric test was carried out to determine calcium levels in green beans (Vigna radiata L.). This titration was carried out directly with murexid indicator and using Na2EDTA as a titrant. The end point is indicated by a color change from pink to violet. From the research that has been done, the calcium level in green beans (Vigna radiata L.) is 0.220% w/w.